2014
DOI: 10.1155/2014/239270
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Au Electrocatalysts for Hydrogen Evolution Reaction at Neutral pH

Abstract: Pd-Au codeposits with different ratio of both metals were electrodeposited on carbon felt, characterized by scanning electron microscopy, and investigated as electrocatalysts towards hydrogen evolution reaction in neutral phosphate buffer solution. The quantities of the produced hydrogen gas with different electrocatalysts, estimated from data obtained by chronoamperometry, were confirmed by mass spectrometry analysis. The highest hydrogen evolution rate was achieved with the electrocatalysts, produced from el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In our previous study [26], the current response at different potentials was monitored and in parallel the produced gases were analyzed by an MS detector. The quantity of the produced hydrogen was independently calculated in two ways: first, based on the area of the corresponding mass spectrometer signals, m/e ¼ 2 (for hydrogen) and second, by integration of areas under chronoamperometric curves obtained at each potential and applying Faraday's law.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study [26], the current response at different potentials was monitored and in parallel the produced gases were analyzed by an MS detector. The quantity of the produced hydrogen was independently calculated in two ways: first, based on the area of the corresponding mass spectrometer signals, m/e ¼ 2 (for hydrogen) and second, by integration of areas under chronoamperometric curves obtained at each potential and applying Faraday's law.…”
Section: Resultsmentioning
confidence: 99%
“…The electrocatalytic activity of electrodeposited PdeAu alloys has been studied in strong acidic and alkaline solutions towards the oxygen reduction reaction (ORR) [24] as well as in a neutral phosphate-citrate buffer for both O 2 and H 2 O 2 electroreduction [23,25]. Applying the electrodeposition conditions described elsewhere [23,25], in our previous study [26] we produced co-deposits with different content of Pd and Au on carbon felt and investigated their electrocatalytic activity towards HER in neutral phosphate buffer solution (PBS) with respect to potential application as cathodes in MECs. The results of this study showed that the increase of the gold content in the electrodeposition bath enhanced the electrocatalytic activity of the obtained electrodeposits and the highest hydrogen evolution rate was achieved with the electrocatalysts, produced from electrolyte with equal mass concentrations of PdCl 2 and HAuCl 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The amount of gaseous hydrogen obtained at different electrodes was estimated to comply with chronoamperometry data. The highest rate of hydrogen evolution was achieved on electrodes obtained from an electrolyte with an equal content of Pd and Au [28]. These studies inspired the authors [29] to synthesize electrodes from Pd-Ag.…”
Section: Fig3 Linear Tafel Polarization Curves Recorded On the Analmentioning
confidence: 74%
“…The ECSA was obtained by dividing the experimental capacitance (C dl ) by the specic capacitance (C sp ), where C sp was taken as 0.025 mF cm À2 , the most reported value for carbonaceous materials. 73,74 Co-MOF1 showed a higher ECSA than Co-MOF2 (13.36 cm À2 and 12.55 cm À2 , respectively), revealing that Co-MOF1 presents an enhanced electrocatalytic activity related to its smaller particle size.…”
Section: (Photo)electrocatalytic Characterizationmentioning
confidence: 94%